MEANING AND SIGNIFICANCE OF GOD-TALK - Nandhikkara, Jose (Journal of Dharma, 2012)
God-talk is part of human language use and forms a kind of unity from a varied and interconnected complex network of different languages. All are not of equal value, but they overlap and crisscross, witnessing and contributing to the richness of religious experience, shedding light both on the mystery of God and human being. God-talk is something fundamental for believers not because of any epistemic or phenomenological properties, but by virtue of the place it occupies in their lives. God-talks are, by nature, for empirical verification. That does not mean that they are not real. The truth value, cognitive value, and semantic value are different in God-talk from other forms of language-games like science, literature, and history. Because the rules of the games are different one should not judge one discourse with the rules of another discourse. Paying attention to the rules of God-talk and their use in religious forms of life is the wisdom that Journal of Dharma follows in preparing this issue on "God-Talk: Horizons."